Improved stabilization scheme for extreme ultraviolet quantum interference experiments. (6th April 2022) - Uhl, Daniel; Wituschek, Andreas; Bangert, Ulrich; Binz, Marcel; Callegari, Carlo; Di Fraia, Michele; Plekan, Oksana; Prince, Kevin Charles; Cerullo, Giulio; Giannessi, Luca; Danailov, Miltcho; Sansone, Giuseppe; et al.
Abstract: Interferometric pump–probe experiments in the extreme ultraviolet (XUV) domain are experimentally very challenging due to the high phase stability required between the XUV pulses. Recently, an efficient phase stabilization scheme was introduced for seeded XUV free electron lasers (FELs) combining shot-to-shot phase modulation with lock-in detection Wituschek et al (2020 Nat. Commun. 11 883). This method stabilized the seed laser beampath on the fundamental ultraviolet wavelength to a high degree. Here, we extend this scheme including the stabilization of the XUV beampath, incorporating phase fluctuations from the FEL high gain harmonic generation process. Our analysis reveals a clear signal improvement with the new method compared to the previous stabilization scheme.